Analisis Rasio Keuangan dalam Menilai Kinerja Profitabilitas dan Likuiditas Perusahaan pada PT. Matahari Departement Store Periode 2023-2024 - Dea Elsani; Roza Fitrialis; Tika Rahmadani; Nayla Riska Vania; Nur Fitriana (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to evaluate the financial performance of PT. Matahari Department Store Tbk for the 2023–2024 period using financial ratio analysis, particularly profitability and liquidity ratios. The study applies a descriptive quantitative approach, utilizing secondary data from the company’s financial reports. Profitability ratios such as Net Profit Margin, Return on Assets (ROA), and Return on Equity (ROE), along with liquidity ratios including Current Ratio, Quick Ratio, and Net Working Capital Ratio, were used as indicators. The results show a significant increase in profitability ratios, indicating improved operational efficiency and asset utilization. Meanwhile, the liquidity ratios also improved but remained below the optimal level, suggesting that the company still faces challenges in meeting its short-term obligations. In conclusion, PT. Matahari has demonstrated enhanced profitability but needs to strengthen its liquidity position to ensure financial stability.